Critical thinking : tools for evaluating research - Nardi, Peter M. (University of California Press, 2017)
"Critical Thinking : A Methodology for Interpreting Information 'deconstructs' common errors in thinking and teaches students to become smarter consumers of research results. Written to complement a textbook or a collection of readings, this brief methods book strengthens students' ability to interpret information whenever and wherever data are used. It includes a wide range of examples along with end of chapter exercises for further discussion. This book will be a coursebook for the undergraduate social science courses where critical thinking, numeracy, and data literacy are common learning objectives"--Provided by publisher.